An approach to highly efficient filtration of methane hydrate slurry for the continuous hydrate production. (15th November 2022) - Xiao, Peng; Dong, Bao-Can; Li, Jia; Zhang, Hong-Liang; Chen, Guang-Jin; Sun, Chang-Yu; Huang, Xing
Abstract: A continuous process for gas hydrate production is of great significance to hydrate–based technologies. In this study, filtrating hydrate particles from hydrate slurries, which is a key step for continuous hydrate production based on water–in–oil emulsion, was systematically studied. The specific resistances of the hydrate cakes formed from different emulsions and under different pressure drops were measured. The results showed that the specific resistance of the hydrate cake increased with the increase of the pressure drop in two stages, and it increased much more rapidly in the second stage. Increasing the concentrations of Span 20, TBAB and PE would increase the specific resistance. The resistances of the hydrate cakes formed with Span 20 + TBAB were much higher than that with Span 20 or Span 20 + PE. Calculation results suggested that only when TBAB with concentration ≥0.25 wt% was used as the anti–agglomerant, the filtration rate could not meet the requirement of a hypothetical production task. An approach that involves filtration mediums, additives and pressure drops was proposed to efficiently filtrate hydrate slurries for continuous hydrate production. Based on the results, a process for continuous hydrate production from water–in–oil emulsion was proposed. Highlights: A pilot plant for gas hydrates production is constructed. Specific resistances of hydrate cakes are measured under different conditions. Filtration rates for different operating conditions are calculated. A conceptual process for continuously producing gas hydrates is proposed. An approach to highly efficient filtration is proposed.